The effect of incubator humidity on morbidity and mortality in preterm infants: a systematic review - Zhiqin Chen; Ruizi Lin; Huixin Wang; Bijun Shi; Qian Chen (BMC Pediatrics)
Abstract Purpose To assess the association between different incubator humidity levels and clinical outcomes in preterm infants. Background Since there is no well-accepted standard for delivery of incubator humidity for preterm infants. A meta-analysis is needed to summarize the status of current research. Methods Databases searched included PubMed, MEDLINE, the Cochrane Library, Embase, Ovid, Google scholar and Web of Science, published between January 2000 and December 2023. Randomized control trials, prospective cohort studies and retrospective cohort studies were included if they assessed how different incubator humidity levels affected preterm infants with a gestational age < 34 weeks, published in English. Infection rates, the incidence of bronchopulmonary dysplasia and predischarge mortality were evaluated. Results Included in this review were 3 randomized control trials and 3 cohort studies including 801 preterm infants. Findings revealed that a high humidity level increased the incidence of infection in preterm infants (RR = 1.26, 95% CI 1.02, 1.55, P = 0.03). No significant difference was found between a high incubator humidity level and the incidence of bronchopulmonary dysplasia or infant mortality. Conclusions This study found that high humidity levels had a significant impact on the incidence of infection. Current evidence is limited by signifcant heterogeneity across studies, lack of data related to regarding the effects of factors such as humidity duration and humidity adjustment schemes on the outcomes.